Studies on the Removal of Indigo Carmin from Aqueous Solutions by GO, Oxidized MWCNTs, AC, and MWCNTs - Shahryar Abbasi; Hadi Noorizadeh (علوم بهداشتی ایران, 2018)
Background and purpose: Quick removal of dye from water and waste water is very important in the research related to eliminating pollutions; this is because of the spread of damaging effects of dyes in water on the human beings and the environment. Four different carbon nanostructures, namely graphene oxide, oxidized multiwalled carbon nanotubes, activated carbon, and multiwalled carbon nanotubes were applied as adsorbents for the removal of Indigo Carmin (IC) dye from aqueous solution. Materials and Methods: These carbon nanostructures were determined by X-ray diffractometer and scanning electron microscope. Batch adsorption experiments were then performed to investigate the effect of solution pH, concentration, contact time, and temperature on IC removal. To study the characteristics of IC adsorption process, adsorption constants were calculated by first-order and pseudo second-order models. Results: Adsorption equilibrium was indicated with Freundlich and Langmuir isotherm models. This study was the first research conducted on the removal of dye which uses four carbon nanostructures adsorbents. Conclusion: The results indicated better efficiency for GO in IC removal than other carbon adsorbents. The isotherm parameters for the Freundlich and Langmuir models were calculated. The kinetics research also revealed that the experimental data was well fitted by pseudo second-order equation.